2014
DOI: 10.4143/crt.2013.084
|View full text |Cite|
|
Sign up to set email alerts
|

Is Prophylactic Irradiation to Para-aortic Lymph Nodes in Locally Advanced Cervical Cancer Necessary?

Abstract: PurposeThis study evaluated the efficacy of extended field irradiation (EFI) in patients with locally advanced cervical cancer without para-aortic nodal involvement.Materials and MethodsA total of 203 patients with locally advanced cervical cancer (International Federation of Gynecology and Obstetrics [FIGO] stage, IB2-IIIB) treated with radiotherapy at Keimyung University Dongsan Medical Center from 1996 to 2010 were retrospectively analyzed. The median patient age was 59 years (range, 29 to 83 years). None o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…The five-year OS rate in the EFRT arms was 67% and 52% in RTOG trial 79-20 and RTOG trial 90-01, respectively [21,23]. Recent institutional series showed 5 year OS rates of 73.5% and 72.4%, respectively [24,25]. The 5 year survival rate in our study was superior to those in the previous studies, suggesting that SEFRT excluding the upper PALN does not significantly compromise PALN control, survival outcomes, and toxicities compared with EFRT.…”
Section: Discussionmentioning
confidence: 99%
“…The five-year OS rate in the EFRT arms was 67% and 52% in RTOG trial 79-20 and RTOG trial 90-01, respectively [21,23]. Recent institutional series showed 5 year OS rates of 73.5% and 72.4%, respectively [24,25]. The 5 year survival rate in our study was superior to those in the previous studies, suggesting that SEFRT excluding the upper PALN does not significantly compromise PALN control, survival outcomes, and toxicities compared with EFRT.…”
Section: Discussionmentioning
confidence: 99%
“…However, OS and DFS were not significantly different between the two groups ( 34 ). In retrospective studies conducted by Yi et al ( 35 ), Oh et al ( 36 ), Park et al ( 37 ), and Yap et al ( 38 ), patients with cervical cancer did not benefit from prophylactic EFI. In the study by Park et al ( 37 ), 203 patients with LACC were included.…”
Section: Prophylactic Efi Combined With Concurrent Chemotherapymentioning
confidence: 90%
“…Prophylactic EFI and pelvic radiotherapy were performed in 88 and 115 patients, respectively. In the pelvic radiotherapy and prophylactic EFI patient groups, the 5-year OS rates were 74.8 and 71.7% ( p = 0.699), respectively, and the DFS rates were 74.5 and 75.8% ( p = 0.668), respectively ( 37 ). It should be noted that in most retrospective studies, the baseline characteristics were not balanced between the two groups.…”
Section: Prophylactic Efi Combined With Concurrent Chemotherapymentioning
confidence: 99%
“…40 Studies using concurrent chemoradiotherapy (CCRT), the current standard of care in LACC, 10,41,42 did not confirm these findings, 43,44 and subsequent studies focused on the treatment of patients with either radiologically or surgically confirmed PALN disease.…”
Section: Management Paln Disease At Diagnosismentioning
confidence: 99%